Exploratory Investigation of Brain MRI Lesions According to Whole Sample and Visual Function Subtyping in Children With Cerebral Visual Impairment - Sakki, Hanna; Dale, Naomi J.; Mankad, Kshitij; Sargent, Jenefer; Talenti, Giacomo; Bowman, Richard (Frontiers in Human Neuroscience, 2022)
Abstract Background: There is limited research on brain lesions in children with cerebral visual impairment (CVI) of heterogeneous etiologies and according to associated subtyping and vision dysfunctions. This study was part of a larger project establishing data-driven subtypes of childhood CVI according to visual dysfunctions. Currently there is no consensus in relation to assessment, diagnosis and classification of CVI and more information about brain lesions may be of potential diagnostic value. Aim: This study aimed to investigate overall patterns of brain lesions and associations with level of visual dysfunction and to compare the patterns between the classification subgroups in children with CVI. Method: School-aged children with CVI received ophthalmological and neuro-psychological/developmental assessments to establish CVI-related subtyping. Other pediatric information was collected from medical records. MRI scans were coded according to a semi-quantitative template including brain regions (right hemisphere, left hemisphere, visual pathways) and summed for total scores. Non-parametric analyses were conducted. Results: 28 children had clinical brain MRI scans available (44% of total sample, Group A (lower severity of visual dysfunctions) n=16, Group B (higher severity) n=12). Total brain scores ranged between 0-18 (Group A mdn=7, IQR=0.8-10.0, Group B mdn=10, IQR=6.5-11.8) and were widespread across regions. 71 per cent had post-geniculate visual pathway damage. The median total brain and hemisphere scores of Group B were higher than subgroup A but differences did not reach statistical significance. No statistically significant associations were found between brain scores and vision variables (acuity, contrast sensitivity). Conclusions: This study found a spread of lesions across all regions on the brain scans in children with congenital CVI. The majority had damage in the postgeniculate visual pathways and visual cortex region suggesting this is an area of interest and potentially informative for diagnosis. However the subtyping classification did not show differences in number or region of lesions though the trend was higher towards Group B. This study confirms the complex diffuse and variable nature of brain lesions in children with congenital CVI, many of whom have other neurological impairments.